Hybrid systems biology : Fourth International Workshop, HSB 2015, Madrid, Spain, September 4-5, 2015. Revised selected papers /: Fourth International Workshop, HSB 2015, Madrid, Spain, September 4-5, 2015. Revised selected papers. (2015) - Unknown
No abstract available